CHALLENGES AND ISSUES OF WOMEN ENTREPRENEURSHIP IN RURAL DEVELOPING ECONOMIES (International Journal of Food and Nutritional Sciences, 2022)
This study intends to discuss the problems concerning women's entrepreneurship in rural India. This paper is frequently based totally on primary and secondary data and some observations; for the identification of these problems, the author has reviewed different articles and reports. Findings of this study reveal that absence of precise schedule of lifestyles, absence of balance between family and career obligations of women, terrible degree of monetary freedom for women absence of direct possession of the property, the paradox of entrepreneurial skill & finance in economically wealthy and poor women, no awareness about capacities, low ability to undergo risk, problems of work with male workers, negligence by financial institutions, lack of self-self-belief, loss of expert schooling, mobility constraints and absence of interaction with a successful entrepreneur are predominant issues of women entrepreneurship development in India.